First evidence of Babesia venatorum and Babesia capreoli in questing Ixodes ricinus ticks in the Czech Republic - Venclikova, Kristyna; Mendel, Jan; Betasova, Lenka; Hubalek, Zdenek; Rudolf, Ivo (Annals of agricultural and environmental medicine, 2015)
INTRODUCTION AND OBJECTIVE: Ixodes ricinus is the most common tick species occurring in Central Europe and it serves as a principal vector of emerging human pathogens. The aim of this study was to determine the prevalence of Babesia spp. in host-seeking I. ricinus in urban and natural habitats. MATERIALS AND METHODS: PCR was applied on samples to assess prevalence of Babesia spp. in questing ixodid ticks. Sequencing was used for Babesia species determination. RESULTS: 1,473 I. ricinus ticks (1,294 nymphs, 99 males and 80 females) were examined for the presence of Babesia spp. at the two study sites. Minimum infection rate for Babesia spp. was found to be 0.5% (infected I. ricinus nymphs were only detected in the natural ecosystem). Two Babesia species were identified by sequencing: B. venatorum (formerly called Babesia sp. EU1) and B. capreoli. CONCLUSIONS: The results obtained represent the first evidence of the occurrence of B. venatorum and B. capreoli in host-seeking I. ricinus ticks in the Czech Republic.
Keywords: Nymph; Ixodes; Babesia; DNA bakterií; RNA ribozomální 18S; Arachnid Vectors; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Female; klíště; zvířata; arachnida jako vektory; sekvenční analýza DNA; Cities; nymfa; DNA, Bacterial; ženské pohlaví; Male; Czech Republic; polymerázová řetězová reakce; Polymerase Chain Reaction; Animals; RNA, Ribosomal, 18S; Česká republika; mužské pohlaví; velkoměsta